Metacognitive Awareness of Reading Strategies as Predictors of Reading Comprehension Achievement among Students with Learning Disabilities in Nigeria - Lazarus, Kelechi Uchemadu; Anwalimhobor, Blessing I. (Indonesian Journal of Disability Studies, 2023)
Reading is an essential language skill in students’ educational success. However, reports have shown that the most prevalent type of academic difficulties among secondary school students with learning disabilities is reading difficulties. Previous studies focused more on interventions to improve reading comprehension achievement of students with learning disabilities than on the influence of metacognitive strategies on students’ reading comprehension achievement. This study, therefore, investigated the influence of metacognitive awareness of (before, during and after) reading strategies on the reading comprehension achievement of students with learning disabilities in Senior Secondary Schools (SSS) in Ibadan, Nigeria. The study adopted a descriptive research design. A sample of 100 students with learning disabilities was purposively selected from nine SSS in Ibadan, Nigeria. Instruments used were Academic records, Screening Checklist for Suspected Learning Disabilities, English Language Achievement Test, Metacognitive Awareness of Reading Strategies Questionnaire and the Reading Comprehension Test. Data collected were analyzed using the Multiple regression analysis at 0.05 level of significance. There was a joint contribution of the independent variables (metacognitive awareness of before, during and after reading strategies) to reading comprehension achievement (F(3,96)=3.61; R2=0.101). The result also reveals the relative contributions of metacognitive awareness of reading strategies (before, during and after) to the reading comprehension achievement among students with learning disabilities as follows: before (β = 0.25), after (β = 0.23) and during (β = -0.17) reading strategies. The study concludes that metacognitive awareness of (before, during and after) reading strategies influence reading comprehension achievement of students with learning disabilities. It is therefore recommended that students with learning disabilities should be trained on the use of metacognitive (before, during and after) reading strategies for improved reading comprehension achievement.